2014
DOI: 10.17557/tjfc.28375
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Water Use Efficiency and Î"13C Isotope Discrimination of Safflower (Carthamus tinctorius L.) under Drought Stress

Abstract: Drought stress is one of the most limiting factors in agricultural productivity because of its highly negative effect on photosynthesis and growth of plants. The main objectives of this study were to determine the performance of four selected safflower genotypes (Remzibey, Dinçer, Balcı and TRE-ASL09/14) against drought stress. The relationship between water use efficiency (WUE) and δ 13 C (isotope discrimination) was investigated under well watered (60%) and drought stress (30%) irrigation in controlled condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…WUE can be considered as a mechanism of stress tolerance and leads to an increase in productivity due to changes in water use (Canavar et al 2014). The decrease of WUE after the period of stress will result in a reduction in the productivity of these lines, indicating a greater susceptibility to water stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WUE can be considered as a mechanism of stress tolerance and leads to an increase in productivity due to changes in water use (Canavar et al 2014). The decrease of WUE after the period of stress will result in a reduction in the productivity of these lines, indicating a greater susceptibility to water stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is an oilseed crop, from the Asteraceae family, not very popular compared to other oil crops such as soybean, sunflower and peanut because it is not widely cultivated around the world (Canavar et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several researches, the sunflower crop positively responds to soil water availability. Farahvash et al, (2011) and Canavar et al, (2014) reported a strong relationship between productivity and irrigation. Moreover, Nezami et al, (2008) indicated that excessive or drought conditions resulted in a reduction in the structural and productive traits of sunflower.…”
Section: Introductionmentioning
confidence: 96%
“…Iran is from arid and semi-arid regions and finding ways to overcome water deficiency has been always from research priorities to produce crops for growing population, because in those regions, drough is an important factor limiting crop production (Soleymani et al, 2011;Ghaffari et al, 2012;Soleymani & Shahrajabian, 2012;Esmaeili & Soleymani, 2013;Canavar et al, 2014;Hajiboland et al, 2014;Hajiboland et al, 2015;Ashraf et al, 2016;Soleymani et al, 2016;Shahrajabian & Soleymani, 2017;Shahrajabian et al, 2017;Soleymani & Shahrajabian, 2017). A technique for efficient management of irrigation water is to use new models for determining water demand and scheduling irrigation along with decreasing the susceptibilty of crop to water deficiency and improving their tolerance to drought by breeding (Soleymani et al, 2012), some of these models estimate the yield under water stress condition (Geerts & Raes, 2009), and others are related to climatic changes and evaluate the yearly variations of the yield during drought periods (Jones et al, 2003).…”
Section: Introductionmentioning
confidence: 99%